Pedagogic Approach in the Surgical Learning: The First Period of “Assistant Surgeon” May Improve the Learning Curve for Laparoscopic Robotic-Assisted Hysterectomy - Favre, Angeline; Huberlant, Stephanie; Carbonnel, Marie; Goetgheluck, Julie; Revaux, Aurelie; Ayoubi, Jean Marc (Frontiers in Surgery, 2016)
Background: Hysterectomy is the most frequently surgery done with robotic assistance in the world and has been widely studied since its emergence. The surgical outcomes of the robotic hysterectomy are similar to those obtained with other minimally invasive hysterectomy techniques (laparoscopic and vaginal) and appear as a promising surgical technique in gynaecology surgery. The aim of this study was to observe the learning curve of robot-assisted hysterectomy in a French surgical center, and was to evaluate the impact of the surgical mentoring. Methods: We retrospectively collected the data from the files of the robot-assisted hysterectomies with the Da Vinci® Surgical System performed between March 2010 and June 2014 at the Foch hospital in Suresnes (France). We first studied the operative time according to the number of cases, independently of the surgeon to determine two periods: the initial learning phase (Phase 1) and the control of surgical skills phase (Phase 2). The phase was defined by mastering the basic surgical tasks. Secondarily we compared these two periods for operative time, blood losses, Body Mass Index (BMI), days of hospitalisations and uterine weight. We finally studied the difference of the learning curve between an experimented surgeon (S1) who practised the first the robot-assisted hysterectomies and a less experimented surgeon (S2) who first assisted S1 and then operated on his own patients. Results: 154 robot-assisted hysterectomies were analysed. 20 procedures were necessary to access to the control of surgical skills phase. There was a significant decrease of the operative time between the learning phase (156.8 minutes) compared to the control of surgical skills phase (125.8 minutes, p=0.003). No difference between these two periods for blood losses, BMI, days of hospitalisations and uterine weight were demonstrated. The learning curve of S1 showed 20 procedures to master the robot-assisted hysterectomies with a significant decrease of the operative time while the learning curve of S2 showed no improvement in operative time with respect to case number. Conclusion: 20 robot-assisted hysterectomies are necessary to achieve control of surgical skills. The companionship to learn robotic surgery seems also promising, by improving the learning phase for this surgical technique.